2020
DOI: 10.5551/jat.50633
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Obesity-Related Indices and Metabolic Syndrome with Subclinical Atherosclerosis in Middle-Aged Untreated Japanese Workers

Abstract: The official journal of the Japan Atherosclerosis Society and the Asian Pacific Society of Atherosclerosis and Vascular Diseases Original Article Aim: Obesity is a social problem due to the prevalence of the Western lifestyle. In particular, visceral fat accumulation, which is a main component of metabolic syndrome, is closely associated with the progression of atherosclerosis. This study aimed to investigate the relationships of obesity-related indices and metabolic syndrome with subclinical atherosclerosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
5
20
1
Order By: Relevance
“…These findings are in agreement with Csige et al [ 41 ] and Sugiura et al [ 42 ]. It is reported that obesity has an association with abnormal function and structure of myocardial muscle with an increased risk for the development of subclinical myocardial damage, as indicated by higher levels of cardiac troponin-T(hs-cTnT) [ 43 ], a similar result to the current study.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in agreement with Csige et al [ 41 ] and Sugiura et al [ 42 ]. It is reported that obesity has an association with abnormal function and structure of myocardial muscle with an increased risk for the development of subclinical myocardial damage, as indicated by higher levels of cardiac troponin-T(hs-cTnT) [ 43 ], a similar result to the current study.…”
Section: Discussionsupporting
confidence: 94%
“…Carotid plaque was found in 1,110 of the 7,730 enrolled individuals. Most of the enrolled individuals were classified as H0 grade (i.e., laboratory assays as described previously 32) . Concentrations of glycated hemoglobin A1c (HbA1c) were measured by high-performance liquid chromatography and expressed according to the National Glycohemoglobin Standardization Program.…”
Section: Resultsmentioning
confidence: 99%
“…The IMT of the carotid artery was assessed by ultrasound using the Aplio 500 device (Canon Medical Systems, Otawara, Japan), as described previously 32) . All estimations of carotid IMT and plaque were performed by well-trained clinical laboratory technicians who were blinded to other clinical information.…”
Section: Assessment Of Carotid Imtmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance underlies the metabolic syndrome, which consists of visceral obesity, hypertension, hyperglycemia, and dyslipidemia 53,54) . Therefore, there is an emerging interest in the relationship between arterial stiffness and visceral obesity and/or metabolic syndrome 53) .…”
Section: Reference Range Of Carotid Stiffness Parametermentioning
confidence: 99%